進路選択で能力・興味の「可能性」を重視する学生の進路意識,発達経験に関する研究 - 菊地, 則行 (進路指導研究, 1988)
The purposes of this study are to examine the following matters of college students who think possiblities of their abilities and interests important in their career-choices: (1) How do they view their career-choices? (2) How do they think about their abilities and interests? (3) What sort of impressing experiences have they had in their life history? (4) What sort of difficulties do they have in their career-choices? (5) What tasks do they wish to achieve or what tasks do they think they must achieve? Subjects are 188 freshmen of faculty of social welfare. Main results are followings; (a) 73.4 % of the subjects regarded "possibilities of their abilities and interests" as important factors in their career-choices. And their purpose of career-choices is to choose the goals of their life. (b) They believed that they could develop their abilities and interests. (c) 70-90 % of them reported some sort of impressing experiences in their life history. Only 40-60 %, however, of them had those experiences relating to their career-choices. (d) The main difficulties many of them had were the lack of career-knowledge and of the knowledge of how to carry out their career-plan. (e) The major task they wish to achieve for their fruitful career-choices is to acquire adequate and accurate knowledges about career and how to carry out their career-plan, and the abilities required in their expected posts.